Navigating Disruption: E-Learning Adoption and Digital Pedagogy Challenges in Traditional Islamic Boarding Schools - Mohammed Al-Hamadi; Rasha Al-Ansari; Ma'mun Mukhid (Islamic Studies in the World, 2025)
Digital transformation in education has accelerated rapidly, presenting both opportunities and disruptions for traditional Islamic boarding schools (pesantren) that have long relied on face-to-face, text-centered, and teacher-led instructional traditions. The shift toward e-learning environments challenges established pedagogical norms, teacher authority, and communal learning structures that are central to pesantren identity. The growing pressure to integrate digital tools highlights the need to understand how pesantren negotiate pedagogical, technological, and cultural tensions during this transition. This study aims to analyze the extent of e-learning adoption, identify the key challenges faced by teachers and students, and examine how digital pedagogy aligns—or conflicts—with traditional Islamic educational practices. A mixed-methods design was employed, combining surveys from 220 teachers and students in selected pesantren with in-depth interviews involving kyai, ustadz, and senior students. Descriptive and inferential analyses were conducted to assess levels of digital readiness, perceived usefulness of e-learning tools, and barriers encountered during implementation, while thematic analysis captured cultural and pedagogical insights. The findings reveal low-to-moderate levels of digital adoption, constrained primarily by limited infrastructure, low digital literacy, and concerns about maintaining adab and discipline in online environments. Teachers reported significant challenges in designing digital instructional materials, while students experienced decreased engagement and difficulty adapting to self-directed learning. Despite these obstacles, some pesantren demonstrated innovative hybrid models that preserved traditional learning values while incorporating digital platforms. The study concludes that successful e-learning transformation requires culturally responsive digital pedagogy, targeted training for educators, and institutional strategies that harmonize technology with pesantren’s spiritual-communal ethos.